Prospective Molecular Epidemiological Study on Transmission of Pulmonary Tuberculosis and Migration (MuT Study) - Bischof, U.; Becher, H.; Dreweck, C.; Haas, W.; Richter, E.; Niemann, S.; Junghanss, T. (Methods of Information in Medicine, 2004)
Introduction: In Western Europe prevalence and incidence of tuberculosis in the indigenous population is declining and TB in migrants from high prevalence countries is becoming a major issue of TB control. Resulting changes in transmission patterns need to be investigated to adapt control strategies. The MuT (Migration and Tuberculosis) study a co-operation among federal and local public health services (ÖDG), the National Surveillance Center (RKI) and the University has been established in Baden-Wuerttemberg to address these issues.Objectives: The goal of this ongoing study is to determine the transmission dynamics of TB in Baden-Wuerttemberg. Here, we present the first set of data on TB cases and their contacts and discuss strategies to overcome arising difficulties.Methods: Prospective data collection of culture positive pulmonary tuberculosis cases and their contacts. Analysis of (1) routine data, (2) spatial data, (3) social interaction data, (4) molecular typing data, and (5) observational data of the implementation phase.Results: The study demonstrates the capability of the study consortium to identify clusters. It provides valuable insights into current case detection and case management procedures and shows ways to improve. A set of factors has been identified that (a) facilitate and (b) discourage study participation.Conclusion: Collaboration among federal and local public health services (ÖGD), National Surveillance Center (RKI) and the University is a promising approach to investigate and improve TB control. This model has potentials for other infectious disease control.
Keywords: Tuberculosis; public health services; migration; molecular epidemiology; clustering